(untitled) (Vietnam Journal of Community Medicine, 2021)
The study was designed according to descriptive epidemiological research through an analytical cross-sectional investigation. Directly interviewing 434 male students of general medical education with the goal: Identifying some factors related to knowledge and practice of tobacco harm prevention and control among male students of university general medicine Thai Binh Medicine and Pharmacy in 2020. Research results show: there is a relationship between the subject’s age and the subject’s smoking behavior with OR = 2.0. Awareness of diseases acquired by passive smoking and subjects’ smoking behavior, according to which subjects who do not know the diseases acquired by passive smoking are more likely to smoke than the know group 4.7 times.